2005
DOI: 10.1124/dmd.104.002568
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Endotoxin-Induced Changes in P-Glycoprotein Expression on Disposition of Doxorubicin in Mice

Abstract: ABSTRACT:P-glycoprotein (PGP) encoded by the Mdr1 gene mediates the excretion of drugs in organs such as the liver and kidney. Inflammation has been shown to suppress the expression and activity of PGP in rodent liver, thus potentially altering the pharmacokinetics of drugs that are substrates of PGP. Here we examined the effect of endotoxin (lipopolysaccharide; LPS)-induced inflammation on the disposition of the PGP substrate doxorubicin (DOX) in the mouse. Male CD-1 mice received 5 mg/kg LPS intraperitoneall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 26 publications
4
50
1
1
Order By: Relevance
“…Moreover, the P-gp and CYP3A levels in the liver and intestine were not coordinately regulated, which is consistent with the findings of Lown et al (1994), who showed that the hepatic CYP3A4 activity in humans did not correlate with the intestinal CYP3A4 activity and protein content. Such tissue-specific response of P-gp and/or CYP3A expression to treatment has been reported by other researchers (Hartmann et al, 2005) and is thought to facilitate the removal of potentially toxic substances in abnormal states where the excretory capacity of a specific organ is diminished. There is evidence that curcumin may modulate the transcription of CYP3A through the pregnane X receptor (PXR) (Liu et al, 2006).…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, the P-gp and CYP3A levels in the liver and intestine were not coordinately regulated, which is consistent with the findings of Lown et al (1994), who showed that the hepatic CYP3A4 activity in humans did not correlate with the intestinal CYP3A4 activity and protein content. Such tissue-specific response of P-gp and/or CYP3A expression to treatment has been reported by other researchers (Hartmann et al, 2005) and is thought to facilitate the removal of potentially toxic substances in abnormal states where the excretory capacity of a specific organ is diminished. There is evidence that curcumin may modulate the transcription of CYP3A through the pregnane X receptor (PXR) (Liu et al, 2006).…”
Section: Discussionmentioning
confidence: 84%
“…Nevertheless in both species, a decreased PGP protein expression is seen (Tang et al, 2000;Hartmann et al, 2001;Goralski et al, 2003). Subsequent pharmacokinetic studies confirmed the fact that inflammation-mediated decreases in the hepatic expression of Mdr1a/PGP in endotoxin-treated mice and rats were associated with corresponding changes in function and significant reductions in the hepatic accumulation and biliary clearance of model substrates including doxorubicin and 99m Tc-sestamibi (Hartmann et al, 2005;Wang et al, 2005).…”
Section: Regulation Of Drug Transporters In Inflammation (Mp-m)mentioning
confidence: 85%
“…Endotoxin-induced down-regulation of PGP/ Mdr1a in brain tissues has also been found to increase intracranial drug accumulation in rodents. Increased accumulation of doxorubicin, which corresponded to decreased PGP protein expression, was observed in the brains of endotoxin-treated mice (Hartmann et al, 2005). Likewise, systemic and CNS inflammation produced by i.p.…”
Section: Regulation Of Drug Transporters In Inflammation (Mp-m)mentioning
confidence: 89%
See 1 more Smart Citation
“…Others have also reported infection or inflammation-mediated increases in the mRNA and protein expression of MDR1 in kidney (Hartmann et al, 2005;Heemskerk et al, 2010). Increased renal expression of MDR1 in endotoxin-treated mice was associated with increased renal elimination of the MDR1 substrate doxorubicin (Hartmann et al, 2005). It is plausible that malaria-imposed changes could impact renal clearance of antimalarials and other substrates.…”
Section: Discussionmentioning
confidence: 99%